Advancing antimicrobial strategies for managing oral biofilm infections - Jiao, Yang; Tay, Franklin R.; Niu, Li-na; Chen, Ji-hua (International journal of oral science, 2019)
Effective control of oral biofilm infectious diseases represents a major global challenge. Microorganisms in biofilms exhibit increased drug tolerance compared with planktonic cells. The present review covers innovative antimicrobial strategies for controlling oral biofilm-related infections published predominantly over the past 5 years. Antimicrobial dental materials based on antimicrobial agent release, contact-killing and multi-functional strategies have been designed and synthesized for the prevention of initial bacterial attachment and subsequent biofilm formation on the tooth and material surface. Among the therapeutic approaches for managing biofilms in clinical practice, antimicrobial photodynamic therapy has emerged as an alternative to antimicrobial regimes and mechanical removal of biofilms, and cold atmospheric plasma shows significant advantages over conventional antimicrobial approaches. Nevertheless, more preclinical studies and appropriately designed and well-structured multi-center clinical trials are critically needed to obtain reliable comparative data. The acquired information will be helpful in identifying the most effective antibacterial solutions and the most optimal circumstances to utilize these strategies.